Jiang-Zhi granules decrease sensitivity to low-dose CCl4 induced liver injury in NAFLD rats through reducing endoplasmic reticulum stress - Lili Yang; Yan Zhou; Haiyan Song; Peiyong Zheng (BMC, 2019)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) may increase the sensitivity to liver injury caused by stimulants such as drugs and poisons. The traditional Chinese medicine (TCM) Jiang-Zhi Granule (JZG) has been proven effective for improving liver function, reducing hepatic fat accumulation and inflammation in NAFLD. The purpose of this study is to evaluate the effect of JZG on the susceptibility of NAFLD rats to liver injury and to identify the relevant mechanism. Methods Forty wistar rats were randomly divided into five groups, normal group, normal+CCl4 group, high-fat diet (HFD) group, HFD + CCl4 group, and HFD + CCl4 + JZG group. NAFLD were established with HFD for 8 weeks. Then Low-dose CCl4 was given intraperitoneally to induce liver injury in NAFLD rats for 48 h. From the 5th week of HFD, intragastric administration of JZG was simultaneously given to the rats in the HFD + CCl4 + JZG group. At the end of the experiment, liver histological pathology, serum transaminase, lipid in liver and blood, as well as hepatic expression levels of endoplasmic reticulum stress (ERS) related molecules were evaluated. Results NAFLD rat model was established by eight-week HFD feeding, exhibiting elevated levels of hepatic lipid, blood lipid, serum transaminase and significantly increased expression of ERS related molecules including glucose regulating protein 78 (GRP78), protein kinase RNA-like endoplasmic reticulum kinase (PERK), eukaryotic translation initiation factor 2α (EIF2α), and nuclear factor-kappa B (NFκB) in liver tissues. After injection of CCl4 in NAFLD rats, elevated serum transaminases, severe inflammation and focal necrosis were observed in liver tissue, but no obvious change was found in the rats of normal group. JZG reduced hepatic inflammation, hepatic necrosis, hepatic lipid, blood transaminases and blood lipids in HFD + CCl4 rats. ERS related molecules were significantly elevated by low-dose CCl4 in NAFLD rats, and were down-regulated by JZG. Conclusion The sensitivity to CCl4-induced liver injury is increased in NAFLD rats, which could be improved by JZG. The pharmacological mechanism may involve the regulation of ERS signaling pathway by JZG.